Outdoor Sofa with Storage Compartment - Achsan, Abdul Aziz; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2023)
In Malaysia, the majority of outdoor sofas are subject to environmental humidity and direct sunlight. The quality of the cushion may be harmed if it subjects to all those types of climatic conditions for a lengthy period of time. Therefore, the purpose of this study is to determine the design criteria for designing and fabricating a prototype of an outdoor sofa with storage compartments. This study employs a questionnaire to collect data. Based on the finding from the questionnaire, the majority of respondents preferred an outdoor sofa having square or rectangle legs with canyon brown finishing color, and dark colour for cushions. Based on the inputs acquired through the simple final design survey, the final design was decided. The prototype was built in accordance with the approved design. In line with this study, an outdoor sofa may increase the life of its cushions by storing them when not in use beneath the seat in built-in storage spaces where they are protected from weather-related damage.